HIKMAH MEMAHAMI GERHANA BULAN DENGAN AYAT-AYAT AL-QUR’AN - Muhamad Aldi; Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses a natural phenomenon, namely a lunar eclipse which is integrated with verses of the Qur'an. A lunar eclipse is a natural phenomenon where the moon is between the moon's shadow because the position is parallel to the moon, earth, and sun. When an eclipse occurs, Islam teaches us to increase worship such as sunnah eclipse prayers, increase dhikr, istighfar and prayer. From an Islamic perspective, a lunar eclipse is one of the signs of the greatness of Allah SWT. By understanding the lunar eclipse, we can learn and take wisdom from the phenomenon of a lunar eclipse. A lunar eclipse is also a moment to reflect on sins, increase istighfar, and get closer to Allah SWT with eclipse prayers (khusuf prayers). There are so many lessons and wisdom that we can take from studying the signs of the greatness of Allah SWT such as this lunar eclipse phenomenon by studying it through the Qur'an and integrating it with scientific evidence will increase our faith and piety to the creator of this universe. Allah SWT provides guidance and guidance through the verses of the Qur'an which have no doubt in them. By understanding the phenomenon of this lunar eclipse, we as Muslims are increasingly aware of the importance of studying and understanding science about the universe. This provides an opportunity for Muslims to improve their understanding and skills in the fields of astronomy, science and technology, and can apply them in everyday life with full gratitude and devotion to Allah SWT.